Tinjauan Yuridis Terhadap Tindak Pidana Aktivitas Judi Togel Online (Studi Kasus Putusan Nomor 349/Pid.B/PN Kwg) - Santosa, Surya Adela Dimas; Faridah, Hana (Jurnal Ilmiah Wahana Pendidikan, 2024)
Online lottery gambling is the same as lottery gambling, in general, both online and offline gambling games, including the drawing of numbers, with the winner having the same number as the one purchased. This online lottery game can be done anywhere. Only a laptop or smartphone is needed to participate in this gambling. Because of the strong correlation between the growth of the internet and the growth of the online gambling industry (internet gambling). Whereas the regulation regarding online lottery gambling in decision number 349/Pid.B/2022/PN Kwg, still applies the articles in the Criminal Code, the judge should have decided on the defendant with article 45 paragraph 2 of Law Number 19 of 2016 Concerning Information and Transactions Electronic. Bearing in mind the principle that applies in Indonesia, namely the principle of lex specialis derogat legi generali (specific law overrides general law). This study uses a normative juridical method with a case approach.